The Healthy Taiwanese Eating Approach is inversely associated with all-cause and cause-specific mortality: A prospective study on the Nutrition and Health Survey in Taiwan, 1993-1996 - Chuang, Shao-Yuan; Chang, Hsing-Yi; Fang, Hsin-Ling; Lee, Shu-Chen; Hsu, Yueh-Ying; Yeh, Wen-Ting; Liu, Wen-Ling; Pan, Wen-Harn (PloS one, 2021)
Few longitudinal studies have investigated the association between foods/dietary pattern and mortality risk in the Asian population. We investigated the prospective association between foods/dietary pattern and risk of death among ethnic Chinese adults in Taiwan. The study population included 2475 young and middle-aged adults (aged 18-65 years at baseline) who completed the questionnaires and physical examinations in the Nutrition and Health Survey in Taiwan from 1993 to 1996. A food frequency questionnaire was administered to assess food consumption habits in a face-to-face interview. With survey data linked to the Taiwanese Death Registry, Cox proportional hazard model was used to identify the foods associated with all-cause mortality(followed until 2012), which were then tallied to calculate a dietary pattern score called Taiwanese Eating Approach(TEA) score. The TEA scores were then associated with various kinds of mortality outcomes. In addition, data from 431 elders (aged≥65 yrs) with 288 death endpoints were used to conduct a sensitivity analysis. A total of 385(15.6%) participants died (111 cardiovascular related deaths and 122 cancer related deaths) during the 17.8-year follow-up period(41274 person-years). Twelve foods (9 inverse [vegetables/fish/milk/tea](+1) and 3 positive[fatty meats/fermented vegetables/sweet drinks](-1)) were significantly associated with all-cause mortality risk. All adults were grouped by their cumulative food score into three diet groups: poor diet(29.3% of all subjects), average diet(44.0%), and healthy diet(26.70%). The better the diet, the lower the total, cardiovascular, and other cause mortality outcomes (trend-p < .001). The hazard ratio for the healthy diet was 0.64 (95% confidence interval:0.47-0.87) for total mortality, and 0.52(0.28-0.95) for cardiovascular death, compared with the poor diet in the multivariable models. This phenomenon was also seen in older adults for all-cause, cancer, and other cause mortalities. Consuming a healthy Taiwanese Eating Approach (TEA) diet is negatively associated with all-cause, cardiovascular, and other-cause mortalities in Taiwan.